2019
DOI: 10.5483/bmbrep.2019.52.12.249
|View full text |Cite
|
Sign up to set email alerts
|

TOMM20 as a potential therapeutic target of colorectal cancer

Abstract: Translocase of outer mitochondrial membrane 20 (TOMM20) plays an essential role as a receptor for proteins targeted to mitochondria. TOMM20 was shown to be overexpressed in various cancers. However, the oncological function and therapeutic potential for TOMM20 in cancer remains largely unexplored. The purpose of this study was to elucidate the underlying molecular mechanism of TOMM20’s contribution to tumorigenesis and to explore the possibility of its therapeutic potential using colorectal cancer as a model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…We found that TOMM20 is expressed in human chondrosarcomas and when overexpressed in chondrosarcoma cells, increases expression of markers of cancer aggressiveness and promotes tumor growth. These data suggest that TOMM20 expression promotes tumor growth by promoting mitochondrial metabolism, increasing proliferation, and inducing markers of an epithelial to mesenchymal transition (EMT), which are consistent with other studies showing an association between TOMM20 expression and outcomes in human cancers [26] [27] [28] [29] [30]. These changes in Journal Pre-proof chondrosarcoma cells induced by TOMM20 overexpression also induce resistance to cell cycle specific chemotherapy agents.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We found that TOMM20 is expressed in human chondrosarcomas and when overexpressed in chondrosarcoma cells, increases expression of markers of cancer aggressiveness and promotes tumor growth. These data suggest that TOMM20 expression promotes tumor growth by promoting mitochondrial metabolism, increasing proliferation, and inducing markers of an epithelial to mesenchymal transition (EMT), which are consistent with other studies showing an association between TOMM20 expression and outcomes in human cancers [26] [27] [28] [29] [30]. These changes in Journal Pre-proof chondrosarcoma cells induced by TOMM20 overexpression also induce resistance to cell cycle specific chemotherapy agents.…”
Section: Discussionsupporting
confidence: 89%
“…We studied the expression of the translocase of the outer mitochondrial membrane subunit 20 (TOMM20) in human chondrosarcomas. High TOMM20 expression has been described in human epithelial and lymphoid cancers and is associated with poor outcomes [26] [30]. We describe for the first time that TOMM20 is highly expressed in high grade compared to low grade human chondrosarcomas, suggesting that aggressive chondrosarcomas have increased mitochondrial metabolism.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The mechanism by which 20(S)-GRh2 regulates cell death and energy metabolism was next elucidated. 20(S)-GRh2 influenced the protein levels of VDAC1 and HK2, which are important regulators of glucose metabolism (45,46), and the changes in VdAc1 and HK2 protein levels were inversely associated. Treatment with 20(S)-GRh2 inhibited mitochondrial metabolism, leading to dissociation of HK2 from mitochondrial VdAc1, which regulated the transfer of Bax to the mitochondria and allowed cytochrome c to enter the cytosol via the outer mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that as MMP decreases, mitochondrialspecific protease presenilin-associated diamond-shaped protein (PARL) and mitochondrial processing peptidase (MPP) are inactivated, and thus resulted in regulation of PINK1 levels (15). Recent studies have reported that TOMM20 plays an essential role as a receptor for proteins which can target mitochondria (16). However, the mechanism of maternal methionine cycle disorders that represses autophagy during neural tube development is still not clear.…”
Section: Introductionmentioning
confidence: 99%